Davidson on turing: rationality misunderstood? - Kuczynski, John Michael (2005)
Alan Turing advocated a kind of functionalism: A machine M is a thinker provided that it responds in certain ways to certain inputs. Davidson argues that Turing’s functionalism is inconsistent with a certain kind of epistemic externalism, and is therefore false. In Davidson’s view, concepts consist of causal liasons of a certain kind between subject and object. Turing’s machine doesn’t have the right kinds of causal liasonsto its environment. Therefore it doesn’t have concepts. Therefore it doesn’t think. I argue that this reasoning is entirely fallacious. It is true that, in some cases, a causal liason between subject and object is part of one’s concept of that object. Consequently, to grasp certain propositions, one must have certain kids of causal ties to one’s environment. But thismeans that we must rethink some old views on what rationality is. It does not mean, pace Davidson, that a precondition for being rational is being causally embedded in one’s  environment in a certain way. If Turing’s machine isn’t capable of thinking (I leave it open whether it is or is not), that has nothing to do with its lacking certain kinds of causal connectionsto the environment. The larger significance of our discussion isthis: rationality consists either in one’s ability to see the bearing of purely existential propositions on one another or rationality is simply not to be understood as the ability see the bearing that propositions have on one another.